An IoT-Based Monitoring and Control System for Chrysanthemum Cultivation - Elva Puspita Wardani; Muhammad Ajik Al Khusain; Sri Kusumastuti; Sihono (JAICT, 2025)
Chrysanthemum cultivation in greenhouse environments requires stable control of environmental conditions, particularly air temperature, light intensity, and soil moisture, to ensure optimal plant growth. However, conventional manual monitoring and control methods still face limitations in terms of efficiency and accuracy. This study aims to design and implement an Internet of Things (IoT)-based monitoring and control system for chrysanthemum cultivation using the NodeMCU ESP8266 microcontroller. The system is equipped with a DHT22 sensor for air temperature, a BH1750 sensor for light intensity, and a capacitive soil moisture sensor v2. Measurement data are transmitted in real time to a Firebase Realtime Database and displayed through the ChrysoSmart mobile application, which supports both automatic and manual operating modes. System testing was conducted directly in a chrysanthemum greenhouse to evaluate sensor performance, actuator operation, and data communication stability. The test results indicate that the system is capable of real-time monitoring and control of greenhouse environmental conditions, with average sensor errors of 0.99% for temperature, 1.11% for light intensity, and 2.96% for soil moisture. The actuators, including a water pump, lighting system, and exhaust fan, operated properly according to system logic and user commands. Therefore, the ChrysoSmart system is considered feasible and effective for supporting automated and remote environmental management in chrysanthemum greenhouse cultivation.